2007
DOI: 10.1002/ceat.200700148
|View full text |Cite
|
Sign up to set email alerts
|

Coal to Liquid (CTL): Commercialization Prospects in China

Abstract: Production of fuels/chemicals from syngas (CO + H 2 ) is receiving increased attention with the background of the resource depletion and the unstable prices of petroleum oil. The fuels, especially diesel, obtained from the syngas conversion via Fischer-Tropsch synthesis (FTS), are proved to be of very high quality that will contribute much to environmental protection and raising the energy efficiency in the transportation sector when modern diesel engines are massively applied in vehicles. FTS technologies dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“…Currently, two demonstration CTL plants, each with a capacity of 160 000 tons per year (ca. 3500 bbl d À1 ), will be commissioned between 2008 and 2009 [33]. The experience gained from these demonstration projects, especially in the field of process engineering, will be expected to pave the way to further scale-up to a truly commercial-scale plant.…”
Section: Historical Development Of the Fischer-tropsch Synthesis Processmentioning
confidence: 99%
See 3 more Smart Citations
“…Currently, two demonstration CTL plants, each with a capacity of 160 000 tons per year (ca. 3500 bbl d À1 ), will be commissioned between 2008 and 2009 [33]. The experience gained from these demonstration projects, especially in the field of process engineering, will be expected to pave the way to further scale-up to a truly commercial-scale plant.…”
Section: Historical Development Of the Fischer-tropsch Synthesis Processmentioning
confidence: 99%
“…Notably, recent progress in the high-temperature (260-290 C) slurry F-T synthesis developed at Synfuels China has pushed productivity to even higher levels. Today, at least double productivity may be achieved due not only to the use of highly efficient F-T synthesis catalyst formulations but also to improved slurry reactor systems [33].…”
Section: Slurry-bed Reactor Technologymentioning
confidence: 99%
See 2 more Smart Citations
“…As a successful example to substitute oil with coal, the conversion route of coal-syngas-methanol-olefi ns has been commercialized in China [4,5] . In the meantime, several industrial projects are being demonstrated or are in pilot-plant test, involving coal to liquid fuels [6] , coal to SNG [7] , coal to glycol [8,9] , and coal to aromatics [10] . In this review, we exceptionally focus our attention on a not as yet outstanding, but potentially important process of coal to acetylene, since it is closely related to the chlor-alkali industry in China.…”
Section: Introductionmentioning
confidence: 99%